Study of the generation and diffusion of bioaerosol under two aeration conditions. (December 2020) - Han, Yunping; Yang, Tang; Han, Chao; Li, Lin; Liu, Junxin
Abstract: Given that studies on actual sewage treatment plants are often affected by environmental conditions, it is challenging to clearly understand the associated bioaerosol generation and diffusion characteristics during the aeration process. Therefore, to enhance understanding in this regard, in this study, bioaerosol generator was used to simulate bioaerosol generation and diffusion under two aeration modes, i.e., bubble bottom aeration and brush surface aeration. The total concentration range of culturable bacteria in the bioaerosol produced by bubble bottom aeration and that produced by brush surface aeration were 300–3000 CFU/m 3 . Under bubble bottom aeration, the generated bioaerosol was symmetrically distributed around the source point, whereas under brush surface aeration, it was primarily distributed in the forward direction of the rotating brush surface. These bioaerosols from bubble bottom aeration predominantly consisted of particles with sizes below 3.3 μm, particularly those with sizes in the range 1.1–2.1 μm. On the contrary, the bioaerosols produced via brush surface aeration predominantly consisted of particles with sizes above 3.3 μm. The distribution characteristics of population structure in the two aeration modes were consistent with the distribution characteristics of concentration in the corresponding models. Additionally, the results showed that when the aeration process is unaffected by environmental conditions (particle matters, wind direct, wind speed, etc.), the bioaerosol components originate primarily from the parent sewage or sludge, and do not diffuse far from the source point. Therefore, source reduction (capping or sealing) can be recommended as the primary control strategy for bioaerosols in sewage treatment plants. The adoption of such measures will significantly limit the diffusion of bioaerosols, thereby reducing the potential risks associated with human exposure. Graphical abstract: Image 1 Highlights: Generation and diffusion of bioaerosols during aeration were simulated. Bioaerosol was symmetrically distributed around the source point under bubble bottom aeration. Bioaerosol was distributed in the forward direction of the rotating brush surface under brush surface aeration. Particle size of bioaerosols from bubble bottom aeration was predominantly <3.3 μm. Particle size of bioaerosols from brush surface aeration was predominantly >3.3 μm.